Socio-Economic and Political Impact of Pandemics in the African Continent and Regional Mechanisms to Mitigate it - Khan, Sultan (International Journal of Criminology and Sociology, 2021)
Throughout the history of African societies, pandemics have claimed, in some instances more lives than warfare. Africa is susceptible to many pandemics. Given the state of underdevelopment amongst African nation-states characterised by low levels of education, poor health care facilities, lack of basic infrastructure, poverty, low levels of income, lack of skilled health care workers, and many more factors, it is not sufficiently equipped to handle pandemics that are life-threatening. Hence, it is prone to outbreaks of infectious diseases. Pandemics cause the socio-economic crisis, which in turn affects political stability. In the history of Africa, the Ebola disease, HIV/Aids, Cholera are some of the major diseases that have ravished nation-states in contemporary times. Now, just like other parts of the world, it has to deal with the Covid-19 pandemic that has far-reaching consequences. This article seeks to interrogate the nature and causes of major pandemics in the globe and the African continent and the steps taken to ameliorate these. It further examines the impact of pandemics on the socio-economic and political spheres of life in the continent.